The Influence of Corporate Governance on Audit Quality: A Systematic Literature Review - Syefi Octaviani Wijaya; Stevani Wijaya; Fanny (Komunitas Dosen Indonesia, 2025)
TThis systematic literature review examines the influence of corporate governance (CG) on audit quality (AQ), addressing gaps in existing research, particularly in emerging markets. It highlights critical factors such as variability in CG practices and AQ outcomes, emphasizing the roles of gender diversity, board independence, and audit committee effectiveness. The objective is to identify key patterns and gaps, offering actionable insights to enhance governance frameworks. Using a rigorous methodology, the study synthesizes findings from recent peer-reviewed research. The analysis focuses on recurring themes like ownership concentration, auditor independence, and audit rotation, employing thematic and narrative synthesis to produce coherent insights. The results demonstrate that independent and diverse boards, effective audit committees, and auditor independence significantly enhance AQ by improving oversight and reducing financial misstatements. However, challenges such as concentrated ownership and weak regulatory enforcement can diminish these benefits. These findings provide valuable recommendations for policymakers and corporate leaders to strengthen transparency, accountability, and stakeholder trust. By integrating theoretical frameworks with practical applications, the study advances global discussions on CG and AQ while highlighting the need for further research in underexplored markets and industry-specific contexts.